2005
DOI: 10.1002/ajhb.20449
|View full text |Cite
|
Sign up to set email alerts
|

The second to fourth digit ratio in elite and non-elite female athletes

Abstract: Contests in the animal world to determine social status almost exclusively involve males, which points out that androgens may be indispensable in the development of competitive instincts. In animal studies, it has been shown that prenatal exposure to androgens may produce permanent changes toward more aggressive behavior in adulthood. Thus, there is a strong suspicion that women involved in competitive activities, such as sports, may have been exposed to high androgen levels in utero. There is strong evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 26 publications
8
60
1
2
Order By: Relevance
“…Similar research reports also show that male 2D: 4D than small females [2][3][4] [5].We know that 2D: 4D in the womb has been determined, 2D: 4D and testosterone levels and sperm counts were negatively; Positively correlated with the concentration of estradiol [6] [7] .Another study showed that male testosterone levels and right-hand 2D: 4D inverse relationship ,between women and men of luteinizing hormone (at right), estradiol (at right and left) and prolactin concentration (in right hand) and 2D : 4D into a positive relationship; Also through the gender, age, height and weight control, right-hand 2D: 4D still and luteinizing hormone and estradiol positive correlation relationship [8] .The report also explains the above documents present research on male 2D: 4D less than girls.…”
Section: A 2d:4d Analysis Between the Results Of Gendersupporting
confidence: 60%
See 1 more Smart Citation
“…Similar research reports also show that male 2D: 4D than small females [2][3][4] [5].We know that 2D: 4D in the womb has been determined, 2D: 4D and testosterone levels and sperm counts were negatively; Positively correlated with the concentration of estradiol [6] [7] .Another study showed that male testosterone levels and right-hand 2D: 4D inverse relationship ,between women and men of luteinizing hormone (at right), estradiol (at right and left) and prolactin concentration (in right hand) and 2D : 4D into a positive relationship; Also through the gender, age, height and weight control, right-hand 2D: 4D still and luteinizing hormone and estradiol positive correlation relationship [8] .The report also explains the above documents present research on male 2D: 4D less than girls.…”
Section: A 2d:4d Analysis Between the Results Of Gendersupporting
confidence: 60%
“…After retrieving a photo on your computer using Photoshop amount of arm length, close to the palm fingers from the crease to the top of the finger, measure out the righthand man of 2D and 4D length [1].20 Photos repeated random sampling volume 2 times, twice before and after the data are highly correlated (right r = 0.99, left r = 0.98). Calculated by SPSS 2D: 4D; right hand 2D: 4D, left hand 2D: 4D, left and right hand 2D: 4D average.…”
Section: B Data Taken:mentioning
confidence: 99%
“…Other investigators have used image analysis to determine 2D:4D from images obtained from flatbed scanners (Bailey and Hurd, 2005;de Bruin et al, 2006;McFadden and Shubel, 2002), radiographs (McIntyre et al, 2005, and digital photographs (Honekopp et al, 2006a;Pokrywka et al, 2005). Bailey and Hurd (2005) showed good intraobserver reliability when a single observer measured finger lengths in 10 subjects using computer-assisted image analysis on hand scans while McFadden and Shubel (2002) showed good interobserver reliability when three observers measured finger lengths using similar computer-based calipers on scanned images of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey and Hurd (2005) showed good intraobserver reliability when a single observer measured finger lengths in 10 subjects using computer-assisted image analysis on hand scans while McFadden and Shubel (2002) showed good interobserver reliability when three observers measured finger lengths using similar computer-based calipers on scanned images of the hand. Investigations using digital photographs of hands pressed against a glass plate also showed good intra and interobserver reliability when using computer programs to measure finger lengths (Honekopp et al, 2006b;Pokrywka et al, 2005). However, it should be noted that the aforementioned studies only performed these small reliability tests to internally validate their observers' ability to measure finger lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation